John Gibbon papers - Gibbon, John 1827-1896.; Grant, Ulysses S. (Ulysses Simpson) 1822-1885.; Ropes, John Codman 1836-1899. (1845)
John Gibbon spent his career in the U.S. Army, serving through the Mexican American War, the Civil War, and the Indian Wars. This collection includes his correspondence with his wife, memoirs and commentary on many aspects of his life and the military, and several miscellaneous items, such as photographs and account books. The collection gives a valuable, broad view of the U.S. Army through the course of three wars. Gibbon comments on many major campaigns of the Civil War, including Gettysburg and Appomattox. He also writes about his command of the 1877 campaign against the Nex Perce Indians under Chief Joseph, and his peace enforcements during the anti-Chinese riots in Seattle in 1886.
This small collection contains mainly correspondence and memoirs from John Gibbon. There are also some miscellaneous materials, including account books from Gibbon's military schooling, scrapbooks, pamphlets, photographs, and a testimonial to Gibbon written by President Ulysses S. Grant.

His correspondence is outgoing to his wife, 1862-1893. Gibbons reports on the military campaigns, particularly the Civil War campaigns in Virginia and his role in the surrender at Appomattox.

The memoirs in this collection include some that were part of his published works, as well as unpublished memoirs on the lessons of war, the education of the army, autobiographical accounts, and a manuscript copy of the "The Army Under Pope," by John C. Ropes, which was published in 1881.

This collection was processed using the More Product, Less Process model, and is not arranged into series. Materials are arranged alphabetically by title.
Cite as: [Indicate cited item or series here], John Gibbon papers (Collection 2031), The Historical Society of Pennsylvania.
This collection was a gift of Mrs. Winthrop H. Battles in 1975.
Gibbon, John. Adventures on the Western Frontier. Edited by Alan Gaff and Maureen Alan. Bloomington: Indiana University Press, 1994. (Call Number F 594.G415 A3 1994)

Gibbon family correspondence, collection 3272
John Gibbon (1827-1896) was a life-long Army officer. He served in the Mexican American War, in the U.S. Army during the Civil War, and in the Indian Wars against the Sioux.

Gibbon was born on April 20, 1827, in Holmesburg, Pennsylvania. Soon after, his family moved to North Carolina, where he graduated from the United States Military Academy and entered his career in the Army. When the Civil War broke out, several of Gibbon's family members were slaveholders and fought in the Confederate infantry. He decided to remain loyal to the Union. Soon Gibbon was promoted through the ranks, and eventually became a Brigadier General for the 4th US Artillery and Western Volunteers, which became known as the Iron Brigade after the Battle of South Mountain.

Although Gibbon temporarily commanded other units when leadership changes occured, such as the 2nd Division of the II Corps at Gettysburg, Gibbon maintained control of the Iron Brigade throughout the war, fighting at the second Battle of Bull Run, Antietam, Fredericksburg, the Wilderness Campaign, Spotsylvania, and commanding them in a successful block of a Confederate retreat at Appomattox Court House. He was one of the three commissioners for surrender for the Confederate Army at Appomattox.

After the Civil War, Gibbon maintained the rank of colonel and fought in Montana against the Sioux, Cheyenne, and Nez Perce in the Indian Wars. He then moved to the Department of the Platte in Seattle, Washington, in 1884 and took control of the command base there. He maintained that position until his death in 1896. He also acted as commander and chief of the Military Order of the Loyal Legion from 1891-1896. He was promoted to the rank of Brigadier General in the U.S. Army in 1885, and he is buried in Arlington National Cemetery.

Gibbon published the 1859 Artillerist's Manual, which was used extensively in the Civil War and later campaigns. He also wrote several works that were published posthumously, including Personal Recollections of the Civil War (1928) and Adventures on the Western Frontier (1994).
Finding Aid Available Online
Keywords: Antietam, Battle of, Md., 1862.; Appomattox Campaign, 1865.; Chinese Americans; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Military Order of the Loyal Legion of the United States; Nez Perce Indians--Wars, 1877.; Sioux nation; Spouses--Correspondence--19th century; United States--History--Civil War, 1861-1865--Military tactics--Union.; United States--History--Civil War, 1861-1865--Personal narratives, Union; United States--History--Civil War, 1861-1865.; United States--History--Mexican War, 1845-1848.; Memoirs; Photographs; Scrapbooks